Effect of VDR and TLR2 gene variants on the clinical course of patients with COVID-19 disease - Kuruca, Nilufer; Atilla, Aynur; Kaya, Muhammed Taha; Gokmen, Sedat; Nursal, Ayse Feyda; Kilic, Ozgur; Kuruoglu, Tuba; Temocin, Fatih; Guvenc, Tolga; Yigit, Serbulent; Guvenc, Dilek (SAGE Publications, 2024)
The coronavirus disease 2019 (COVID-19) pandemic, which has caused a major global health crisis, primarily targets the upper and lower respiratory tract. But infected individuals may experience different clinical symptoms, ranging from asymptomatic to critical. The vitamin D receptor (VDR) and Toll-like receptor 2 (TLR2) polymorphisms play a role in the immune response. This study aimed to evaluate the effect of VDR Bsml (rs1544410) and TLR2 23bp indel variants on the clinical status of Turkish patients with COVID-19 disease. A total of 312 people, including 106 intensive care unit (ICU) patients, 103 symptomatic hospitalized patients, and 103 healthy controls, were included in the study. The VDR BsmI and TLR2 23bp indel were genotyped using polymerase chain reaction and/or restriction fragment length fraction methods. The VDR BsmI b/b genotype and b allele were higher in symptomatic patients compared to the healthy control group ( p   =  0.035). The VDR BsmI B/B and B/b genotype distribution did not differ between ICU patients and both symptomatic patients and controls ( p   >  0.05). We found that B/B:B/b+b/b and B/B+B/b:b/b were significantly different in symptomatic patients compared to controls ( p  = 0.033 and p  = 0.041, respectively). The VDR BsmI b/b genotype distribution was found to be lower in deceased patients than in living patients ( p  = 0.023). There was no significant difference between the groups in terms of TLR2 23bp indel genotype and allele distribution ( p  > 0.05). Our study results suggest that the VDR BsmI b allele may have a role in COVID-19 patients with symptomatic findings. These data need to be repeated in different ethnic and larger sample groups.
Keywords: Male; Adult; Turkey; Genotype; SARS-CoV-2; COVID-19; Middle Aged; Polymorphism, Single Nucleotide; Toll-Like Receptor 2; INDEL Mutation; Case-Control Studies; Humans; Receptors, Calcitriol; Female; Genetic Predisposition to Disease; Alleles; Aged; 3. Good health